Designing an Electronic System for Visual Stimuli and Its Impact on the Accuracy of Setting and Spiking Skills in Volleyball Players - Altoohafi, sajjad; Hussein, Ali; Rajab, Badr (Journal of Physical Education, 2024)
The research aimed to enhance the accuracy of setting and spiking skills among the players of the University of Baghdad’s volleyball team for the academic year (2022-2023) through a visual stimuli system designed by the researcher. The system works to develop the accuracy of two skills simultaneously during the operation of the system, through the accuracy of setting on an electronic board that contains numbers. Based on this, the setter prepares for the required position according to the number displayed on the board. The system also works to enhance the accuracy of spikes through lights that operate simultaneously with the numbers and within the opponent’s area. Based on the location of the light that illuminates the area, the player performs a spike (either straight or diagonal) onto the illuminated area, according to the type of stimulus. This integrated approach not only improves the precision of spiking skills but also provides realistic game scenarios, enhancing training effectiveness. The researcher intentionally employed the experimental method for a single group with both pre-test and post-test. The research population and sample comprised players from the university volleyball team for the 2022/2023 season, who were students of the College of Physical Education and Sports Sciences, totalling 18 players. The research sample was intentionally selected, excluding the libero players, of whom there were 2. In addition to excluding the two players involved in the pilot experiment, the sample size was thus (14) players, representing (77.778%) of this population. Following the procedural steps, statistical analyses, and verification of scientific principles and parameters, the researcher arrived at the final form of the study. The statistical analysis was conducted using the SPSS system to derive conclusions and applications aimed at improving the spatial accuracy of both researched skills based on their correlation with enhancing performance and motor control in the specific parts of each skill. The educational tool helped to define this free activity within the parameters of correct performance through the lighting controlled by the coach to direct the players’ tasks and increase their attention in each part of the performance. This approach also catered to the detailed nuances required to showcase them along with proper skillful performance. Thus, the role of visual stimuli exercises is to facilitate the precise direction of the ball to the designated location through control and manipulation, by accelerating cognitive processes for players and enhancing their effectiveness. On the one hand, they support the motor pathway of the required skillful behaviour and guide it, while also accelerating cognitive processes, or more precisely, increasing their effectiveness in organized training without exaggeration in the training environment. The researcher concluded that exercises involving visual stimuli within an innovative electronic system aid in enhancing the accuracy of the setting skill and improving the accuracy of the spiking skill in volleyball among the players of the University of Baghdad team.